Improving contact durability of polycrystalline systems by controlling the parameters of large-angle grain boundaries - Kopylov, Viacheslav; Kuzin, Oleg; Kuzin, Niсkolay (Eastern-European Journal of Enterprise Technologies, 2019)
Polycrystalline metal systems in the samples made of steel 40X with different morphology and parameters of the distribution of large-angle grains boundaries for energy have been examined. The effect of the structural-energy state of grains boundaries on the operational reliability of improved steel 40X has been established. Based on the hierarchical modeling of polycrystals structure, new approaches have been proposed and algorithms have been developed for defining relationships between the structure that is formed in the technological processing of materials and stages in the life cycle of parts. It has been revealed that it is advisable to use, as a digital prototype of the structure of polycrystalline alloys that describes their performance under conditions of contact loads, the matrix representation of a system model that would incorporate the quantitative characteristics of grains. By using the devised procedures, the ways to execute technological control over the energy state of grain boundaries in the structural components have been defined in order to improve durability of parts exposed under contact loads. An estimation-experimental method has been developed to assess the effect of quantitative characteristics of the structure on the parameters of strength of the grains boundaries and their ability to form intragrain damage under external loads. The energy level of grains boundaries and triple joints between the groups of small and large grains is higher than that between grains of the same size. The boundary surfaces with a high level of energy are places where damage occurs at technological processing and under external loads on structural materials. This points to the crucial role of large-angle boundaries placed between triple joints with a high energy gradient in the process of forming microstructurally short cracks and intragrain destruction of polycrystalline systems. The use of hierarchical modeling methods and computational materials science makes it possible to improve the operational reliability of articles by choosing the optimal parameters for internal boundary surfaces. The lower cost of the parts' life cycle is achieved by thermal treatment regimes, which alter the quantitative characteristics of the steel structure